Microsatellite development and detection of admixture among three sympatric Haploblepharus species (Carcharhiniformes: Scyliorhinidae). Issue 12 (27th July 2020) - van Staden, Michaela; Gledhill, Katie Samantha; Gennari, Enrico; McCord, Meaghen Erica; Parkinson, Matthew; Watson, Ralph Gareth Andrew; Rhode, Clint; Bester‐van der Merwe, Aletta Elizabeth
Abstract: Haploblepharus is an understudied genus comprising four recognized scyliorhinid species that are endemic to southern Africa. Species identification within this group has historically been problematic due to a high degree of morphological conservatism among congeners, further complicated by the possibility of interspecific hybridization. This study describes the development of two microsatellite panels comprising 10 polymorphic markers for the puffadder shyshark, Haploblepharus edwardsii . The markers were characterized in 35 H. edwardsii specimens and tested for cross‐species utility in Haploblepharus fuscus, Haploblepharus pictus, and the more distantly related scyliorhinid Halaelurus natalensis . Genetic diversity statistics were estimated for each species, and the presence of population differentiation was tested for in H. edwardsii and H. pictus . Furthermore, interspecific genetic differentiation was examined to infer the potential use of these markers for species identification as well as for detecting signatures of admixture among Haploblepharus species. All microsatellite markers were polymorphic in each species, with polymorphism information contents ranging from 0.43 to 0.62. Population differentiation was only evident for H. pictus, where genetic discontinuity was detected among geographically distant sampling sites. Statistically significant differentiation (fixation index between populations F ST = 0.091 to 0.382) was found between all species; however, the level of differentiation between H. fuscus and H. pictus was low in comparison and seemingly at a population level rather than at a species level. Species assignment using Bayesian clustering analysis resulted in approximately 57% of 88 genotyped specimens being unambiguously assigned to a distinct genetic cluster that confirmed accurate taxonomic assignment. Overall, the low levels of differentiation together with the presence of distinct and admixed genetic clusters suggests a recent divergence and possible contemporary hybridization within the genus Haploblepharus. As such, conservation strategies should be focused on the generic level until such a time that Haploblepharus species can be readily identified.